2020
DOI: 10.1155/2020/9815465
|View full text |Cite
|
Sign up to set email alerts
|

The Intention on Modern Contraceptive Use and Associated Factors among Postpartum Women in Public Health Institutions of Sodo Town, Southern Ethiopia 2019: An Institutional-Based Cross-Sectional Study

Abstract: Background. The postpartum period is an important transitional time for couples to put the decision on family planning utilization. However, women in Ethiopia are usually uncertain about the use of family planning during this period. This cross-sectional study was, therefore, aimed at determining the intention of modern contraceptive use and associated factors among postpartum women attending the immunization clinic in Sodo town, Ethiopia. Method. This institution-based cross-sectional study was conducted amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
2
4
2
1
Order By: Relevance
“…The prevalence as found in this study may thus be expected to differ from those found in studies that covered larger groups of women. Two, the prevalence found in the current study also differs from the prevalence reported in an existing hospital-based study [43]. Usually, hospital-based studies covered a smaller proportion of childbearing women which often makes the result inconsistent with findings in population-based studies.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…The prevalence as found in this study may thus be expected to differ from those found in studies that covered larger groups of women. Two, the prevalence found in the current study also differs from the prevalence reported in an existing hospital-based study [43]. Usually, hospital-based studies covered a smaller proportion of childbearing women which often makes the result inconsistent with findings in population-based studies.…”
Section: Discussioncontrasting
confidence: 90%
“…This provides support for findings in several existing studies conducted in Nigeria and elsewhere [41,46,47]. Also, the study revealed that several relational characteristics such as partners' education, women's financial autonomy, safer sex negotiation, and participation in household decisions may have a strong influence on the intention to use modern contraceptives in line with findings in previous studies [42,43]. The import of these findings is that the socio-demographic context of rural women cannot be exonerated from poor use or non-intention to use modern contraceptives.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is consistent with a study carried out in Sodo Town, Southern Ethiopia, in which 70% of the participants were willing to use modern contraceptives. 26 It is also similar to findings of a study conducted in Ghana where the magnitude of the intention of postpartum family planning was 70%. 27 The prevalence of modern contraceptive use in this study was low (9.2%).…”
Section: Discussionsupporting
confidence: 88%